(untitled) (TSUL LEGAL REPORT, 2026)
This article examines theoretical rules, concepts, and opinions on the general conditions for verifying the legality, validity, and fairness of judgments, rulings, and decisions, as reflected in the Criminal Procedure Code of the Republic of Uzbekistan. It explores the content and essence of amendments and additions to the procedures for filing a complaint (protest) against a judgment or ruling of the court of first instance, as well as the significance of these innovations in the theory and practice of criminal procedural law and their role in the activities of criminal justice. Additionally, an analysis of the prosecutor’s role as a party in the court of appeal, as a higher instance, and their powers is presented. From the perspective of the new norms of criminal procedural legislation, this scientific work describes modern legal factors of appeals, which serve as mechanisms for reviewing court decisions in criminal cases, and the grounds for canceling or amending court decisions. To highlight the relevance of the topic, the author gives special attention to the opinions and views of procedural scholars in various educational and scientific literature on the science and field of criminal procedural law, the need to revise judicial documents in recent years, and an analysis of the powers and responsibilities of judges in judicial practice in this regard.